PEMBUATAN APLIKASI MULTIMEDIA INTERAKTIF PEMBELAJARAN BAHASA JEPANG LEVEL DASAR - Jessyca Wulandari; Budi Hartanto; Marcellinus Ferdinand Suciadi (Perpustakaan Universitas Surabaya, 2018)
In this increasingly advanced era, mastering a foreign language can provide many advantages, one of them is Japanese language. By looking at these advantages, such as expanding opportunities in the working world, getting scholarships and knowing the culture of the country concerned, then the Japanese language course appears. However Japanese characters which consists of three characters make students difficult to memorize because these characters are too many. In addition, a boring learning method that used by teacher can make students lazy to learn. Therefore, an application that can help the community to understand the Japanese language with role playing learning method is created. In this application, the lesson divided into six stages and delivered briefly. Overall, the user will interact a lot with a female character. This character will guide the user from beginning to the end to tell the user some basic sentence patterns and Japanese characters of hiragana and katakana. Evaluation in this application is given by answering some questions and accompanied by match and pair letter and picture cards mini games. From the test results, it can be concluded that this multimedia application can help beginners to learn Japanese with an interesting appearance and help users in memorizing Japanese characters and without spending any cost.